The Transformation of Halal Certification Policy and Public Response: An Islamic Economic Law Perspective - Safitri, Eka; Cholil, Suhadi (UIN Siber Syekh Nurjati Cirebon, 2025)
This article aims to analyze the government's efforts in implementing halal certification policies in Indonesia and the public's response to the changes in these regulations. The study uses a qualitative approach with an ethnographic method, involving data collection from various digital media sources such as websites, YouTube, Instagram, Twitter, and Facebook. Data collection techniques include identifying primary sources, tracking, annotating, as well as gathering and presenting data. The primary theory used is Islamic economic law, focusing on the principles of justice, transparency, and public welfare within the context of halal certification regulations. The study's findings indicate that digital media plays a crucial role in accelerating the dissemination of information regarding the new halal certification regulations and facilitates two-way communication between the government and the public. Public response reveals complaints regarding the length of the certification process and the government's slow response to community grievances. This article contributes to the development of Islamic economic law research by offering a perspective on integrating sharia principles in public policy and the halal industry practices, aiming for greater justice and transparency.Keywords: public response; Islamic economic law; halal certification regulation; policy transformation.